MEASURES TO PREVENT CAVITATION IN PUMPS (Academicia Globe: Inderscience Research, 2023)
Pump stationinstallation of suction pipes in pump units, its working order plays an important role in its operation and increasing its efficiency. It is precisely due to the rapid bending of the water pump details, the change in the size of the details in the working wheel, and the phenomenon of "cavitation" that occurs in the pump, it has a very negative effect on the efficiency of the pump station. As a result, the pump impeller needs repair before the due date, and the pump stops until the station is stopped.